The Dazzling Comet C/2020 F3 (NEOWISE): The Comet of The Century - Khalil, M.; Said, M.; Osman, H.; Younis, N.; Khaled, N.; Amr, Y.; A. Mohamed, N.; brahim, A. (International Journal of Advanced Astronomy, 2020)
The newfound long period comet NEOWISE has the potential to be one of the brightest comets ever seen. The comet which was visible to the naked eye is considered as the comet of the century. This icy object was discovered on March 27, 2020. In this paper, we dive into some fascinating facts about NEOWISE comet that make such comet unique.Â Â